Observations of waves and currents during barrier island inundation. Issue 4 (13th April 2017) - Engelstad, A.; Ruessink, B.G.; Wesselman, D.; Hoekstra, P.; Oost, A.; van der Vegt, M.
Abstract: Overwash and inundation on barrier islands can transport sediment onshore, leading to vertical accretion. These processes could ensure barrier island growth in times of sea‐level rise, but wave and current fields during overwash and inundation are not well understood. Field data of water levels, waves, and currents were collected on a barrier island in the Netherlands to investigate the hydrodynamics during island inundation. Observations show that even in shallow water depths (<0.5 m) wave energy was not completely dissipated as waves propagated from the North Sea onshore. Additionally, locally generated wind waves entered the field area from the Wadden Sea and propagated offshore. Infragravity waves were an important part of the wave field, particularly onshore of the beach crest. They were observed to be onshore progressive and displayed a bore‐like shape when water depths were shallow. Wave breaking was the dominant dissipation mechanism for high‐frequency waves as well as for infragravity waves, which is in agreement with prior research on infragravity wave energy dissipation on mild sloping (closed‐boundary) beaches. A large‐scale offshore directed water‐level gradient between the Wadden Sea and the North Sea side, caused by elevated water levels in the Wadden Sea during the storms, frequently drove an offshore flow if it was large enough to exceed the cross‐shore gradient due to wave setup. In addition, elevated water levels in the Wadden Sea decreased current velocities due to a decrease in water‐level gradients. This study highlights the influence of back‐barrier processes on the hydrodynamics during inundation. Key Points: Elevated water levels in the Wadden Sea during storms can drive offshore flow during inundation Waves are coming from both sides of the barrier island and lose their energy primarily by wave breaking Infragravity waves crossing the submerged barrier island were onshore progressive, displayed a bore‐like shape and were breaking